Evaluación del sistema de seguimiento a graduados de la universidad técnica de Cotopaxi extensión la maná frente al perfil de formación profesional y propuesta de reingeniería. - Ramón Amores, Sebastián Fernando (2016)
This research has a great importance in the processes that take place in the institutions of higher education, because with the information obtained from monitoring graduates it is possible to improve academic processes in a meaningful way. Within the theoretical argument relevant aspects for research such as evaluation, important aspects of systems, monitoring graduates, professional profile and the most important points in the development of a reengineering were taken into account. This study belongs to the modality of feasible project, that is; it is based on bibliographic and field research and a proposal for intervention. To conduct this research, it has a total population of 315 people including managers, and graduates of the Technical University of Cotopaxi La Maná and was applied to a corresponding sample involved. The objective was to design a model for the monitoring system to graduates of the extension. The proposal was to make a reengineering to reach an improvement in the structure, functioning and organization of the monitoring system for the proper handling of information. The beneficiaries of this proposal are the UTC La Mana, the different careers, graduates and current students of the institution.